“WE STUDY AT THE SAME UNIVERSITY”: SIBLINGSHIP AND ITS ROLE IN EXCHANGE OF SOCIO-CULTURAL CAPITAL AMONG KAZAKHSTANI YOUTH. - Tlepova, Ayan (Nazarbayev University School of Sciences and Humanities, 2024)
Introduction: Well-known assumption that children in the family have little power to influence each other as much or more than their parents seems to be taken for granted, consequently creating a blind point in the examination of interfamilial connections and research of family dynamics. Thus, the current study examines how important siblingship is in connection to changes in individuals’ social and cultural capital in Kazakhstan. Precisely this research gives more perspective on how siblingship can be influential in reality and what patterns and shapes it takes in affecting lives in the context of socio-cultural capital. Therefore, the study will try to explore and answer the following research question: How kinship ties influence development and exchange of social and cultural capital among siblings? Results: After conduction nine semi-structured in-depth interviews, findings show that siblings are able to produce own socio-cultural capital and share it with other children but the process is highly dependent on many factors such as siblings’ age gap, geographical proximity among them, gender dynamic imposed by family and outside communities, and presence in certain life stages – all affecting each other from childhood to adulthood. Conclusion: In order to explore exchange and production of capital among children, it is crucial to look at sibship dynamics and factors that influence their nature, which gives more understanding on why and how capital is created and shared between siblings. Although findings showcase crucial importance of socio-cultural capital production by siblings, relatively homogenous sampling can overlook increasing importance of capital in siblings with lower socio-economic background.
Keywords: Type of access: Open Access; social capital; cultural capital; Pierre Bourdieu; kinship